Screening of potential bacteria with antagonism properties isolated from soil and stream in Hutan UiTM Cawangan Negeri Sembilan / Ida Muryany Md Yasin, Anis Shazlyn Ismail and Nurfasihatul Husna Faizal - Md Yasin, Ida Muryany; Ismail, Anis Shazlyn; Faizal, Nurfasihatul Husna (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Infectious diseases caused by bacteria are increasing nowadays, and this cause the production of synthetic drugs also in demand. However, synthetic drugs give side effects to some people, so to reduce or as an alternative, biotherapeutic treatment can be used using bacteria taken from natural sources that have not been explored by humans which are very sustainable. Therefore, bacteria which are common microorganisms will help to serve critical roles in the health and operation of land and aquatic ecosystems. The study was conducted at Hutan UiTM Cawangan Negeri Sembilan, Kuala Pilah Campus to isolate and characterize the bacterial colonies from soil and stream. The main focus of this study is to identify Gram positive bacteria with negative haemolytic activity and to determine the antagonism activity against pathogenic bacteria. A total of 20 pure bacterial colonies were isolated from soil samples, and 30 from stream samples collected at various locations. Gram positive bacterial identification indicated that 12 out of the 20 soil colonies and 10 out of the 30 stream colonies exhibited characteristics consistent with Gram positive bacteria. Haemolysis test and catalase test were conducted on both Gram-positive bacteria isolated from soil and stream samples where soil samples have seven bacterial isolates and stream samples have eight isolates showed no hemolytic activity, while for catalase test five and four bacterial isolates showed positive activity correspondingly. However, no inhibition zones were observed in the antagonism assays of all isolates from both samples against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Although the antagonism results were negative, this study contributes to our understanding of the microbial diversity in soil and stream water ecosystems. Further research is recommended to refine the experimental procedures, optimize conditions, and employ selective media for more targeted analysis. Such investigations will help unravel the potential applications of bacteria present in soil and stream samples and their ecological roles.